Living in the Information Technology era - Abante, Marmelo (Manila, 2023)
This text describes how the impact of Information Technology has shaped the way we live today. List the various computer-related discoveries and innovations that helped shape Information Technology as it exists now. This book will familiarize students with the history of computers and information technology. They must be able to define the benefits and cons of living in the IT era, be conversant with emerging trends and technologies, and design the potential future of information technology.
Keywords: Information Technology